# How do you convert #y = -x# into polar form?

Polar form of

By signing up, you agree to our Terms of Service and Privacy Policy

To convert the equation ( y = -x ) into polar form, we can use the relations between Cartesian coordinates (x, y) and polar coordinates (r, θ).

In polar coordinates, ( x = r \cos(\theta) ) and ( y = r \sin(\theta) ).

Given ( y = -x ), substitute ( -x ) for ( y ) in the polar coordinate equation:

[ -x = r \sin(\theta) ]

Now, we have the equation in terms of ( r ) and ( \theta ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7